Hubungan antara Sistem Zonasi Sekolah dengan Hasil Belajar Geografi Siswa Kelas XI IPS di SMA N 1 Tualang - Yahya, Rafiki Rahmat; Afdhal, Afdhal (MASALIQ, 2024)
One of the new policies issued by the Ministry of Education and Culture regarding the Admission of New Students (PPDB) is the zoning system. This policy is one of the government's efforts to equalize education. This also directs students to register at the school closest to their domicile. However, at SMA N 1 Tualang there are several phenomena that emerge which create a relationship between the school zoning system and geography learning outcomes. This research aims to determine the relationship between the school zoning system and the geography learning outcomes of class XI IPS students at SMAN 1 Tualang, Siak Regency. The method used in this research is quantitative with a correlational research type. Based on hypothesis testing using the one-way test category with a significance level of 5%, the results showed that the zoning system had a positive effect on the geography learning outcomes of class Students have close and positive relationships. With research results showing that the zoning system influences student learning outcomes, therefore the zoning system needs to be improved.